UPAH PEMBUATAN KANDANG PUYUH DALAM TINJAUAN FIQH MUAMALAH (Studi di Jorong Kamboja Nagari Lubuak Jantan) - Ramadhona Halim Putra; Nurhikma Nurhikma (Jurnal Integrasi Ilmu Syariah (Jisrah), 2021)
The main problem in this study is how to pay wages for making cages in Jorong Cambodia, Nagari Lubuk Jantan, North Lintau Buo District, Tanah Datar Regency, and how to review muamalah fiqh on wages for making quail cages in Jorong Cambodia, Nagari Lubuk Jantan, North Lintau Buo District, Tanah Regency. Flat. The purpose of this study was to find out and explain the wages for making quail cages and explain the fiqh muamalah review of wages for making quail cages in Jorong Cambodia, Nagari Lubuk Jantan, North Lintau Buo District. The type of research that the author uses is qualitative research, while the nature of the research is descriptive qualitative. Qualitative descriptive research is to describe phenomena that occur in the field as they are according to reality. Data collection was carried out using interview and documentation techniques. Based on the results of the research that the author did, it was concluded that the implementation of the wage system in the manufacture of quail cages, the owner of the cage asked for the contents of one box of 40 quails, then the total wages of one box was Rp. 120,000,-. If one row of wages Rp. 9,000,000, - then after the cage is ready, the owner fills a box with 50 quails, then the craftsman suffers a loss in one box of Rp. 30.000,-. one row of 75 boxes, the craftsman suffers a loss of Rp. 2.250.000,- in one row of quail cages. The form of aqad carried out by the owner of the cage with the worker who made the cage verbally, this is not in accordance with the agreement because there is an element of gharar which is not allowed because it will cause harm to one party or a mutual agreement and harm the party concerned. Overview of Fiqh Muamalah on wages in making The quail cage that occurred in Jorong Cambodia Nagari Lubuk Jantan was not in accordance with the Fiqh Muamalah concept because there was a loss caused by one of the parties. Islam forbids anything that harms one of the parties to the muamalah, every loss and harm must be eliminated.